2017
DOI: 10.1007/s11899-017-0393-y
|View full text |Cite
|
Sign up to set email alerts
|

Equal Treatment and Outcomes for Everyone with Multiple Myeloma: Are We There Yet?

Abstract: Multiple myeloma treatment has changed tremendously over recent years leading to overall improvement in patient outcomes. With therapeutic advancements, patient care has become increasingly complex and variability is seen in healthcare delivery as well as outcomes when various patient subgroups are analyzed based on sociodemographic factors. It is imperative to understand this variability so that while overall the outcomes get better, specific focus is placed on subgroups that may remain disadvantaged and may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 52 publications
2
39
0
Order By: Relevance
“…This is mainly because of a rapidly improving therapeutic landscape with novel drugs, better understanding of disease biology, and improvement in supportive care . Despite these encouraging trends, disparities exist in MM outcomes by patient race/ethnicity . Several studies have described these disparities and investigated at their potential causes, and most have reported differences in access to therapeutics options, including novel drugs and stem cell transplantation (SCT) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly because of a rapidly improving therapeutic landscape with novel drugs, better understanding of disease biology, and improvement in supportive care . Despite these encouraging trends, disparities exist in MM outcomes by patient race/ethnicity . Several studies have described these disparities and investigated at their potential causes, and most have reported differences in access to therapeutics options, including novel drugs and stem cell transplantation (SCT) .…”
Section: Introductionmentioning
confidence: 99%
“…3,[5][6][7][8][9] Despite these encouraging trends, disparities exist in MM outcomes by patient race/ethnicity. 2,10 Several studies have described these disparities and investigated at their potential causes, and most have reported differences in access to therapeutics options, including novel drugs and stem cell transplantation (SCT). 2,[11][12][13][14] With changing US population demographics and an increasing proportion of racial/ethnic minorities, comprehensive studies describing differences in various aspects of health care among patients according to racial/ ethnic groups are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…A widening gap among socioeconomic status groups have been shown in the last two decades [67]. In this increasingly complex therapeutic scenario, it is imperative to focus on subgroups that may remain disadvantaged [68].…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…In recent years, with the continuous advent of new drugs and new treatments, the prognosis of patients with MM has been greatly improved. However, not all MM patients bene t equally from these improvements [5]. To explore the causes of this difference, a few studies from the Cancer Registry and the SEER database have shown the impact of racial and socioeconomic status (SES) disparities on the prognosis of patients with multiple myeloma [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%